AUGMENTED REALITY BOOK PENGENALAN BARONG BALI - Gede Sukra Ardipa; Padma Nyoman Crisnapati; I Made Gede Sunarya; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
Balinese Barong is one of the most famous culture items in bali, even so,many Balinese do not know that there are many kinds of barong in Bali. That is caused by people's interest on learning barong as Balinese culture is low. One factor that caused this phenomenon is because of technology development. The purpose of this research is to design and implement applications that can be used as a medium for learning and introduce Balinese Barong with more interactive and attractive by utilizing technology. The research method used is the research and development, to develop Augmented Reality applications Book introduction Balinese Barong, using the waterfall model to the system testing phase. This application uses a library that is able to play sound vuforia explanation and featuring Balinese Barong 3D objects into a real environment with the help of books and android smartphones. The results of this research is a book that contains information and images related to the Balinese Barong and also functioned as a marker of Book-based Augmented Reality applications android capable of displaying objects in the form of Barong Bali just above the 3 dimensional marker complete with voice narration explanation. This application can be used as a medium to introduce and preserve the national culture